Oncolytic viral therapy for pancreatic cancer. Issue 1 (13th April 2017) - Rahal, Ahmad; Musher, Benjamin
Abstract : Outcomes of pancreatic adenocarcinoma (PDA) remain dismal despite extensive clinical investigation. Combination chemotherapy provides modest improvements in survival above best supportive care, and immunotherapy has thus far not proven effective. Nevertheless, growing insight into antitumor immunity and the tumor microenvironment has inspired the discovery of novel agents targeting PDA. Oncolytic viruses represent an emerging class of immunotherapeutic agents that have undergone extensive preclinical investigation and warrant further investigation in well‐designed clinical trials.